Model Faktor Determinan Kompetensi Lulusan Perguruan Tinggi Islam Swasta di Kota Medan - Yudi Siswadi; Radiman Radiman; Jufrizen Jufrizen; Muslih Muslih (Universitas Negeri Medan, 2020)
This study aims to determine how the determinant factor model of competence of graduates of private Islamic tertiary institutions in the city of Medan. The population in this study are all Private Islamic College Students in Medan. The respondents will be taken 135 respondents. Data collection in this research was conducted by means of interviews, questionnaires and documentation. The data analysis method used was the Structural Equation Model. The results showed that Foundation Management affected Governance, Foundation Management affected Lecturer Performance, Foundation Management affected graduate Competence, University Governance affected Lecturer Performance, University Governance affected Graduates' Competence, and Lecturer Performance influenced Graduates Competence. Private Islamic College in the City of Medan. Foundation Management influences Lecturer Performance and Foundation Management influences graduate Competence through governance and University Governance influences graduate Competency through lecturers' performance in Private Islamic Universities in Medan.